PERANCANGAN VIDEO FEATURE WANITA BERHIJAB DALAM KIPRAH MUSIK UNDERGROUND - CENDYANA RIZA CHANIAGO, Dr. Syafwandi, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Underground music is a center of all streams of loud music that becomes an unlimited view of life as a means of expression and becomes a complex that includes the social aspects of each music genre. Whereas underground music for common people is hard music composed of melodic and harmonic compositions which are full of improvisation, coupled with the distinctive shouts or growls brought by the vocalists. In general, this music is more in demand by men, but now no exception women begin to enjoy it. Just like women that wearing hijab (hijab women) are in the gait of underground music, which will be the spotlight for people outside the underground music environment.The purpose of this design is to make a feature video of a hijab woman in an interesting and easy to understand underground music that will be processed creatively, so that it is useful, and raises a new view of the society towards women who like the underground music style and make accurate information.This design will be informed via the video feature media. This video feature is expected to be one medium that is strong enough to convey information because it consists of two elements, namely audio and visual. Data collected from this video feature is done using the method of observation and interviews. A data analysis method using 5W + 1H technique (what, when, where, why, who + how).Kata kunci : Video Feature, Wanita berhijab, Musik Underground